2012
DOI: 10.1074/jbc.m112.399899
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Induces Hepatic Steatosis by Generation of Mitochondrial Oxidative Stress

Abstract: Background: Uric acid is an independent risk factor in fructose-induced fatty liver, but whether it is a marker or a cause remains unknown. Results: Hepatocytes exposed to uric acid developed mitochondrial dysfunction and increased de novo lipogenesis, and its blockade prevented fructose-induced lipogenesis. Conclusion: Rather than a consequence, uric acid induces fatty liver Significance: Hyperuricemic people are more prone to develop fructose-induced fatty liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
547
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 589 publications
(602 citation statements)
references
References 52 publications
16
547
3
7
Order By: Relevance
“…26,27 ChREBP is a glucose-responsive basic/helix-loop-helix/leucine zipper transcription factor that is mainly expressed in liver and specifically binds to a carbohydrate response element containing E box. Activation of ChREBP was reported to occur with fructose, which could be mediated by fructose-induced uric acid generation; 13 however, we were not able to show a direct activation of ChREBP by uric acid. Despite an absence of uric acidinduced activation of ChREBP, our study showed that uric acid increased the cleavage of SREBP-1 into mature form and nuclear translocation.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…26,27 ChREBP is a glucose-responsive basic/helix-loop-helix/leucine zipper transcription factor that is mainly expressed in liver and specifically binds to a carbohydrate response element containing E box. Activation of ChREBP was reported to occur with fructose, which could be mediated by fructose-induced uric acid generation; 13 however, we were not able to show a direct activation of ChREBP by uric acid. Despite an absence of uric acidinduced activation of ChREBP, our study showed that uric acid increased the cleavage of SREBP-1 into mature form and nuclear translocation.…”
Section: Discussioncontrasting
confidence: 91%
“…We have previously reported mitochondrial oxidative stress by uric acid-activated ATP citrate lyase and FAS that led to de novo lipogenesis in liver. 13 In this manuscript, we have identified an additional mechanism whereby uric acid induces hepatic steatosis via ER stress.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations